Representation of Women Power in Beyoncé Knowless’ song “Run The World (Girls)” - Neni Kurniawati (Universitas Dian Nuswantoro, 2021)
Song is one of the propaganda media for ideolgy. Beyonce Knowless's song “Run the World (girls)” is an example of a song that raises the issue of Black Feminism Thought. This paper will discuss how textual and discursive practices through the signs in the text of the song lyrics and video clips of the song in constructing the paradigm of black women power or black feminism thought. By interpreting the structure of the text in the lyrics of the song and the visual signs in the video clip of the song